Effects of High Temperature and Cooling Pattern on the Chloride Permeability of Concrete - Zhiming Ma; Guangzhong Ba; Zhenhua Duan (Advances in Civil Engineering)
Concrete structure is frequently subjected to the fire attack, whereas the permeability of concrete with fire-damage has received little consideration. This paper aims to investigate the chloride permeability of plain concrete and recycled aggregate concrete (RAC) with fire-damage, and the effects of various cooling patterns and recuring treatment on the chloride permeability are also studied. The results manifest that the elevated temperatures result in an increase in the fire-damage and chloride permeability of concrete, and that the increase becomes more obvious with the temperature above 400°C. Attributing to the water-cooling which provides a recuring environment, the chloride permeability after water-cooling is lower than that after air-cooling when the temperature is 200°C. Whereas when the temperature is above 400°C, the chloride permeability after water-cooling becomes higher than that after air-cooling, due to an extra damage that the water-cooling produces. The recuring treatment can reduce the chloride permeability of concrete with fire-damage, and the reduction becomes more significant when the concrete suffers a serious fire-damage. Exposing to the same condition of high temperature, the addition of recycled aggregate (RA) further boosts the fire-damage and chloride permeability of concrete. Particularly, the chloride permeability increases with the increasing of RA replacement ratios, linearly, and the increased temperatures further lead to an increase in the slope of the fitting straight line.